Manajemen Peserta Didik dalam Meningkatkan Motivasi Belajar Siswa - Rizki Akmalia; Aina Ul Mardiyah Ray; Aji Pramudya; Fauzan Azrohid; Laila Ali Tanjung (Departement of Mathematics Education, 2023)
In the educational process, students are active subjects and objects. They are said to be subjects because they play an active role as the main actors in the learning process, while they are said to be objects because they are the targets of students to be developed by educators. 3 If students are used as targets, then they must act as active subjects in learning facilitated by the school, namely one of them is by implementing student management that can stimulate all the potential that exists within them. Growing student motivation is one of the techniques in developing the ability and willingness to learn. One logical way to motivate students in learning is to relate learning experiences to student motivation. Increasing student learning motivation is based on the belief that student learning motivation has implications, not only on the learning outcomes obtained, but also on the benefits of the entire learning process. Slavin argues that motivated students will be easily directed, given assignments, tend to have great curiosity, are active in seeking information about the material explained by the teacher and use higher cognitive processes to learn and absorb the lessons given (Sharif, ).